The Clinical Practice Guidelines, a step forward for the control of Sexually Transmitted Infections in Colombia - Hernando Gaitán-Duarte (Federación Colombiana de Obstetricia y Ginecología, 2013)
This issue of the Revista Colombiana de Obstetricia y Ginecología features the Clinical Practice Guideline (CPG) for the syndromic management of Sexually Transmitted Infections (STIs) in Colombia. This guideline is part of a set of Guidelines developed by the cinetsalliance in response to Grant 500 of 2009 funded by Colciencias at the request of the former Ministry of Social Protection. The development of this guideline required the joint effort of academic institutions and scientific societies in order to provide Colombia with the papers containing the recommendations for the management of patients suffering from some of the diseases of greatest Public Health concern. The Colombian Federation of Obstetrics and Gynecology (fecolsog) had an active participation in the development of this Guideline published today, as well as in the development of the Guidelines for pregnancy and childbirth. Clinical Practice Guidelines (CPG) have been defined as "systematically developed statements to assist practitioner and patient decisions about appropriate health care for specific clinical circumstances" (1). More recently, they were defined as "documents containing recommendations designed to improve patient care. They are built on systematic search for evidence and careful consideration of benefits and harm derived from other management alternatives" (2). It is important to emphasize that guidelines are not only based on evidence, but they must also build on clinical experience and patient experience when it comes to stating recommendations.